2014
DOI: 10.1096/fj.14-252189
|View full text |Cite
|
Sign up to set email alerts
|

20S proteasome activation promotes life span extension and resistance to proteotoxicity in Caenorhabditis elegans

Abstract: Protein homeostasis (proteostasis) is one of the nodal points that need to be preserved to retain physiologic cellular/organismal balance. The ubiquitin‐proteasome system (UPS) is responsible for the removal of both normal and damaged proteins, with the proteasome being the downstream effector. The proteasome is the major cellular protease with progressive impairment of function during aging and senescence. Despite the documented age‐retarding properties of proteasome activation in various cellular models, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(165 citation statements)
references
References 66 publications
(91 reference statements)
12
149
2
2
Order By: Relevance
“…High proteasome activity enhances the removal of damaged proteins and thereby improves the quality of the proteome and the maintenance of proteostasis. This may increase longevity (25,26), and helps the cell to resist oxidative stress (25,27). High levels of proteasome activity have also been seen in other underground-burrowing animals, such as the naked mole rat.…”
Section: Discussionmentioning
confidence: 99%
“…High proteasome activity enhances the removal of damaged proteins and thereby improves the quality of the proteome and the maintenance of proteostasis. This may increase longevity (25,26), and helps the cell to resist oxidative stress (25,27). High levels of proteasome activity have also been seen in other underground-burrowing animals, such as the naked mole rat.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, most of the mammalian proteasome genes are regulated by Nrf2 in response to antioxidants such as 3H-1,2-dithiole-3-thione (D3T) (34). We have previously shown that SKN-1 is involved in proteasome activation in C. elegans following pbs-5 overexpression (8). Moreover, treatment of human fibroblasts with 18a-glycyrrhetinic acid (18a-GA) triterpenoid promotes Nrf2 activation, leading to proteasome activation, and enhanced cellular stress resistance and life span (27).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, proteasome activation has been suggested as a potential antiaging (9) and retardation strategy against the progression of age-related diseases (16). Lately, proteasome activation was achieved in multicellular organisms through genetic manipulation of either 20S or 19S subunits with positive outcomes on aging, stress resistance, and aggregation-related neuropathies (8,55,58). Given the restraints of genetic manipulation in humans, identification of proteasome-activating compounds is needed to promote proteasome enhancement ideally through human normal diet.…”
Section: Introductionmentioning
confidence: 99%
“…The model nematode Caenorhabditis elegans which are widely used as a model in aging studies (Fawcett et al 2015;Chondrogianni et al 2015) were used to study the physiological and molecular changes in a biological system during UV-A exposure. Many natural compounds with antioxidants that have anti-aging activity have been successfully tested in this model (Zheng et al 2014;Sonani et al 2014).…”
Section: Introductionmentioning
confidence: 99%